Lean manufacturing implementation in Malaysian automotive industry: An exploratory study - Nordin, Norani; Md Deros, Baba; Abd Wahab, Dzuraidah (2011)
This paper presents an exploratory study of lean manufacturing implementation in Malaysian automotive industries.A questionnaire survey is used to explore the extent of lean manufacturing implementation.This paper also examines the drivers and barriers that influence the implementation of lean manufacturing.The survey was performed on sixty Malaysian automotive components manufacturing firms.The respondents were chosen from those who are directly involved with lean manufacturing practices such as production and quality personnel.The findings show that most of the respondent firms are classified as in-transition towards lean manufacturing practice.These in-transition firms have moderate mean values for each of the five lean manufacturing practice categories.It is also found that these firms spend more attentions and resources in internal areas such as firms’ operation and management, compared to external relationships with suppliers and customers.These firms believe that the factors that urged the implementation of lean manufacturing are the desire to focus on customers and to achieve the organisation’s continuous improvement.The results from this survey also revealed the main barriers that prevent or delay the lean implementation.The main barriers to implement lean manufacturing system are the lack of understanding lean concepts and shop floor employees’ attitude.